Tantangan Guru dalam Menerapkan Kurikulum Merdeka di Sekolah Dasar: Penelitian - Rahmawati Eka Saputri; Beby Azratul Zahwa; Bernanda Aditra Clorinda; Neesya Herawati; Silvia Syifa Dewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Merdeka Curriculum was introduced as an effort to establish a learning process that is flexible, contextual, and student-centered. The implementation of the curriculum in the classroom greatly depends on the active involvement of teachers. However, the transition to the Merdeka Curriculum has not always proceeded smoothly. This study focuses on uncovering the challenges faced by teachers in implementing the Merdeka Curriculum at the elementary education level. A descriptive qualitative approach was employed, with data collected through interviews and direct observations of teachers at SD Muhammadiyah 4 Tangerang. The findings revealed several obstacles, including limited understanding of the new curriculum concepts, difficulties in adjusting teaching strategies, constraints in developing teaching materials, and challenges in applying differentiated learning in the classroom. Nevertheless, teachers’ enthusiasm to continue growing serves as a key asset in ensuring the successful implementation of the curriculum.